Praskie ratusze – symboliczne czy rzeczywiste centra władzy? - Jišová, Kateřina (Roczniki Dziejów Społecznych i Gospodarczych, 2014)
Town halls in Prague – A symbolic or real centre of power? (Summary) The Prague agglomeration consisted of four medieval towns: the Old Town, the New Town, Mala Strana and also Hradčany. The article throws light on the relations, often dramatic, between the town halls of the Old and New Towns (the fi rst was built in 1338, the second before 1374) in the 15th century. An uprising broke out in the New Town in 1419. The insurgents forced their way into the town hall and defenestrated 10–13 men. In May 1420 the communes appointed new councillors for the first time. In August, on the initiative of Jan Želivský, a general meeting of the communes was convened in the Old Town hall and new councillors were appointed. In June 1421 armed action by the townsmen of the New Town resulted in the town council’s resignation. Both towns were combined into a single body governed from the Old Town hall, of course, under Želivský’s dictatorship. However, the chancelleries of both towns remained independent and maintained town ledgers in parallel. During that period the importance of the town councils’ dropped to an alltime low, political decisions were taken by Želivský, without the participation of either of the town halls (in 1422 Želivský was imprisoned in the Old Town hall and subsequently decapitated). The association of Prague communes disintegrated at the turn of 1423/24. Sigismund Korybut ruled in the period from 1422 to 1427. The Duke established a new joint council for the Old and New Towns, consisting of 18 councillors from both towns. Korybut was overthrown, but everything seems to point to the fact that later both towns were once again unified; however, from August 1428 at the latest, the councils again became independent. In 1434 thanks to the support of Bohemian lords, the townsmen of the Old Town captured the New Town. But in 1436, the Holy Roman Emperor, Sigismund of Luxembourg, who had already accepted a pledge of allegiance from the townsmen of Prague, freed the citizens of the New Town from the Old Town’s hegemony. In 1483 another uprising began in Prague, which was referred to as the epilogue to the Hussite revolution, which claimed new victims from among the authorities of both town halls. Forty years later there were further tensions in Prague.